2001
DOI: 10.1006/dbio.2001.0187
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Factor Bone Morphogenetic Protein 4 Restricts Ductal Budding and Branching Morphogenesis in the Developing Prostate

Abstract: The budding of the urogenital sinus epithelium into the surrounding mesenchyme signals the onset of prostate morphogenesis. The epithelial and mesenchymal factors that regulate ductal budding and the ensuing process of ductal growth and branching are not fully known. We provide evidence that bone morphogenetic protein 4 (BMP4) is a mesenchymal factor that regulates ductal morphogenesis. The Bmp4 gene was most highly expressed in the male urogenital sinus from embryonic day 14 through birth, a period marked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
171
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(186 citation statements)
references
References 48 publications
11
171
0
4
Order By: Relevance
“…On other hand, it should be noted that BMP4, a vertebrate homolog of Drosophila Decapentaplegic, which acts as a downstream target of Shh in other tissue types (for reviews, see Refs. 9 and 51), is found to be expressed in the prostate and shown to inhibit prostatic epithelial branching (53), but its expression is not regulated by Shh based on our RT-PCT analysis (Fig. 8).…”
Section: Discussionmentioning
confidence: 89%
“…On other hand, it should be noted that BMP4, a vertebrate homolog of Drosophila Decapentaplegic, which acts as a downstream target of Shh in other tissue types (for reviews, see Refs. 9 and 51), is found to be expressed in the prostate and shown to inhibit prostatic epithelial branching (53), but its expression is not regulated by Shh based on our RT-PCT analysis (Fig. 8).…”
Section: Discussionmentioning
confidence: 89%
“…Crosstalk between HH and other signaling pathways, such as fibroblast growth factors (Fgfs), bone morphogenetic proteins (Bmps) and Wnts, and integration of these multiple inputs, is likely to be as crucial for regulating normal development of the these tissues as has been proposed in other regions of the developing embryo (Lamm et al, 2001;McMahon et al, 2003;Ovchinnikov et al, 2006;Roberts et al, 1998;Yamada et al, 2006;Zuniga et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have demonstrated that the UGS mesenchyme is the target of several key signals, including testosterone, estrogen and sonic hedgehog (17)(18)(19). UGS mesenchyme is also the origin of several key morphogens including BMP-4, FGF-10, TGFÎČ (20)(21)(22)(23) and Shh target genes such as IGFBP-6 (Lipinski et al, submitted), which may regulate both epithelial and mesenchymal proliferation and differentiation. The complexity of these interactions is daunting.…”
Section: Introductionmentioning
confidence: 99%